THE FOLK CARNIVALESQUE: RESISTANCE AND SUBVERSIVE WIT IN BENGAL’S ALKAP TRADITION - Hoque, Mir Masudul; Shaikh, Md Sujauddin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Alkap, a distinctive form of folk theatre encompassing a vibrant amalgamation of dance, drama, and music, shares its roots with the Jatra tradition. As an indigenous performing art, it once enjoyed widespread popularity in specific districts of West Bengal and Bangladesh, as well as regions spanning Jharkhand and Bihar. Historically, Alkap has served as a source of entertainment for rural communities, captivating audiences with its portrayals of mythological narratives, social injustices, and a myriad of intriguing everyman subjects. However, Alkap’s original charm lay in its capacity for subversion and resistance, as it artfully mimicked the kings and landlords, challenged gender norms through cross-dressing, and infused performances with elements of sexual innuendo, profligate colloquialism, etc. Although the Alkap tradition has largely faded into obscurity, its significance as a platform for social commentary remains paramount within the socio-political matrix of rural Bengal. Through a comprehensive exploration of historical and contemporary Alkap theatre and by analysing the carnivalesque characteristics such as wit, humour, satire, and parody within Alkap performances, this paper explores how Alkap theatre serves as an artistic medium for the expression of social critique and cultural resilience against dominant ideologies and power structures. Furthermore, this research delves into the ways in which Alkap theatre adapts to contemporary socio-economic and political contexts, continuing to be a dynamic force of folk carnivalesque. In conclusion, the study underscores the imperatives for the preservation and revitalisation of this tradition, recognising its potential not only as a source of entertainment but also as a means to foster critical dialogue and societal transformation within rural communities.